Search for charge-parity violation in semileptonically tagged D 0 → K + π − decays - The LHCb collaboration; R. Aaij; A. S. W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A. A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C. A. Aidala; et al. (Journal of High Energy Physics)
Abstract An analysis of the flavour oscillations of the charmed neutral meson is presented. The ratio of D 0 → K + π − and D 0 → K − π + decay rates is measured as a function of the decay time of the D 0 meson and compared with the charge-conjugated system to search for charge-parity violation. The meson flavour at production is double-tagged by the charges of the muon and pion in the preceding B ¯ → D ∗ 2010 + μ − X $$ \overline{B}→ D^{* }{(2010)}^{+}{μ}^{-}X $$ and D ∗(2010)+ → D 0 π + decays, respectively. These decays are selected from proton-proton collision data collected by the LHCb experiment at a centre-of-mass energy of 13 TeV and corresponding to an integrated luminosity of 5.4 fb −1. The flavour oscillation parameters, relating to the differences in mass and width of the mass eigenstates, are found to be y′ = (5.8 ± 1.6) × 10 −3 and (x′)2 = (0.0 ± 1.2) × 10 −4. No evidence for charge-parity violation is seen either in the flavour oscillations or in the decay, where the direct charge-parity asymmetry is measured to be A D = (2.3 ± 1.7) %.